1990
DOI: 10.1007/bf01742496
|View full text |Cite
|
Sign up to set email alerts
|

Addition of interleukin-2in vitro augments detection of lymphokine-activated killer activity generatedin vivo

Abstract: The in vivo administration of repetitive weekly cycles of interleukin-2 (IL-2) to patients with cancer enhances the ability of freshly obtained peripheral blood lymphocytes (PBL) to lyse both the natural-killer(NK)-susceptible K562 and the NK-resistant Daudi targets. Lysis of both targets is significantly augmented by inclusion of IL-2 in the medium during the cytotoxicity assay. This boost is much greater for cells obtained following the in vivo IL-2 therapy than for cells obtained prior to the initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Despite this finding, only the CD25 marker was related to the clinical response, which may be because of the expression of these markers on different P B M C cell subsets. The L A K cytotoxicity determined in this study varied as described in other studies using IL-2 alone, and was not related to the clinical response [2,10]. Only two previous reports have indicated a correlation between L A K cytotoxicity and the clinical response.…”
Section: Resultsmentioning
confidence: 64%
“…Despite this finding, only the CD25 marker was related to the clinical response, which may be because of the expression of these markers on different P B M C cell subsets. The L A K cytotoxicity determined in this study varied as described in other studies using IL-2 alone, and was not related to the clinical response [2,10]. Only two previous reports have indicated a correlation between L A K cytotoxicity and the clinical response.…”
Section: Resultsmentioning
confidence: 64%
“…[7][8][9] Hank et al found that LAK generated by continuous infusion, then exposed to additional IL-2, were significantly more cytotoxic against the Daudi cell line than LAK generated by continuous infusion alone. 14 In our study, we sought to translate the in vitro observation of Hank to melanoma patients by administering continuous infusion followed 24 hours laser by pulse dose IL-2. The single pulse IL-2 dose is based on prior outpatient data.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Hank et al showed in vitro that LAK generated by continuous infusion IL-2 had significantly increased lytic activity against tumor cells when the LAK were subsequently pulsed with IL-2. 14 Horton et al showed that the LAK cytolytic activity of lymphocytes generated by infusional IL-2 then pulsed with IL-2 were equal to the LAK activity of lymphocytes that were cultured up to 7 days in vitro with IL-2. 15 These studies suggest that a combination of first continuous infusion IL-2 to generate higher amounts of LAK cells followed by the superimposition of a pulse dose of IL-2 to further augment tumor-cell killing may offer some theoretical advantage.…”
Section: Introductionmentioning
confidence: 98%
“…[21][22][23][24] Furthermore, Hank et al showed in vitro that LAK produced by constant infusion IL-2, then subsequently pulsed with additional IL-2 displayed significantly greater cytotoxicity against tumor cell lines. 25 Increased lymphocytic infiltration of tumors may be seen in patients receiving famotidine. 26 Famotidine, in vitro, has been shown to increase lymphocyte cytotoxicity against tumor cell lines, possibly by increasing internalization of IL-2 by the IL-2 receptors on natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 98%